Post-activation potentiation's impact on specialized strike strength in elite male boxers: an acute study - Liu, Y.; Jin, R.; Chen, C. (Sensors, 2025)
Objective: The purpose of this study is to investigate the effects of back squat (BS) and squat jump (SJ) on the maximum-striking strength and speed-striking strength of the jab and cross of elite male boxers, and to identify the time point of the post-activation performance enhancement (PAPE) induced by these two activation methods. Methods: A total of 29 Chinese male boxers were recruited to participate in four different intensities of muscle activation through BS and SJ exercises (BS50%, SJ50%, BS80%, SJ80%). The participants were tested on their jab and cross using specialized testing protocols at recovery intervals of 4, 8, 12, and 16 min (speed-striking strength testing was conducted first, followed by maximum-striking strength testing), and the maximum-striking strength and speed-striking strength of the athletes were recorded. Results: (1) Maximum-striking strength: For the jab, the results indicated that there were significant differences between BS50% at 8 min and 12 min and the baseline (p < 0.01), and between SJ50% at 4, 8, and 12 min and the baseline (p < 0.01). BS80% showed significant differences at 12 min compared to baseline (p < 0.01), and the SJ80% exhibited significant differences at 8 min (p < 0.05) and 12 min (p < 0.01) compared to baseline. For the cross, BS50% demonstrated significant differences at 12 min compared to baseline (p < 0.01), and SJ50% showed significant differences at 8 min and 12 min (p < 0.01). Both BS80% and SJ80% revealed significant differences at 8, 12, and 16 min compared to baseline (p < 0.01). (2) Speed-striking strength: For the jab, there were no significant differences between BS50% and SJ50% at all time intervals compared to baseline (p > 0.05). BS80% showed a significant difference at 4 min compared to baseline (p < 0.05), and SJ80% exhibited significant differences at 12 min compared to baseline (p < 0.01). For the cross, there were no significant differences between BS50%, SJ50%, and BS80% at all time intervals compared to baseline (p > 0.05), while SJ80% demonstrated significant differences at 8 min and 12 min compared to between (p < 0.01). The results showed that PAPE significantly enhanced maximum punch force at 8-12 min across several activation conditions. In contrast, improvements in speed-striking force were only observed following high-load squat jump (SJ at 80% 1 RM), with significant increases at 8 min for the cross and at 12 min for the jab, whereas BS or lower-load SJ produced no meaningful changes. Conclusions: PAPE activation significantly enhances the striking force of boxers at the recovery interval of 12 min, but the effect is influenced by the intensity and method of activation. High-load activation can enhance the striking strength of boxers more rapidly and sustainably, and high-load SJ are more beneficial for the speed-striking strength of boxers.